Aberrant origin of right vertebral artery from the arch of aorta - Das, Jayanta (Indian J Thorac Cardiovasc Surg, 2021)
We present a rare case of an aberrant right vertebral artery originating from the arch of aorta distal to the origin of the left subclavian artery. The incidence of this particular variant of aberrant origin of the right vertebral artery is extremely uncommon with only seventeen cases reported in literature to date. This case was incidentally detected on a staging positron emission tomography-computerized tomography (PET-CT) scan for lung cancer. We review the incidence, embryological mechanism, and clinical importance of this aberrant course of the right vertebral artery.